Validity and reliability of the Brazilian version of the Patient Dignity Inventory (PDI - Br) - Suzana Cristina Teixeira Donato; Toshio Chiba; Ricardo Tavares de Carvalho; Marina de Góes Salvetti (Universidade de São Paulo, 2021)
Objective: to perform the psychometric validation of the Brazilian version of the Patient Dignity Inventory (PDI - Br) in patients with advanced diseases in palliative care. Method: a methodological study to verify the psychometric properties of the Patient Dignity Inventory (PDI - Br) instrument, through validity and reliability tests. Results: the exploratory factor analysis showed a factorial solution with three factors, responsible for 40.9% of the explained variance, with adequate internal consistency for the Presence of Symptoms (α=0.859), Dependence (α=0.871), and Existential Suffering (α=0.759) domains. The test-retest was performed and indicated moderate to strong correlations. Convergent validity demonstrated a positive correlation between the Presence of Symptoms and the sadness (r=0.443) and anxiety (r=0.464) variables. Weak negative correlations were observed between the PDI - Br domains and functionality, spiritual well-being and quality of life. Conclusion: composed of three domains and 25 items, the PDI - Br instrument presented satisfactory psychometric properties for its use in our environment, through the evidence of validity and reliability.